Performance of shell-and-tube heat exchangers with different baffles applied to water chillers based on fluid–structure interaction. (28th May 2019) - Wen, Jian; Liu, Yuce; Tian, Jin; Li, Chaolong; Liu, Huaqing; Xiao, Juan; Wang, Simin
Abstract : As one of the substitutes for R134a in chillers, the refrigeration performance of R450A is poor. Heat exchanger structural improvement is proposed to improve its refrigeration performance in chillers. In this article, the heat transfer characteristics, resistance characteristics, and stress characteristics of shell-and-tube heat exchangers (STHXs) with different baffles (segmental baffles [SB], plane helical baffles [PB], fold helical baffles [FB]) are numerically investigated based on the fluid–solid coupling. The results show that the shell-side flow velocity and temperature difference of STHXsSB are the highest, and those of STHXsPB are the lowest. The heat transfer coefficient and pressure drop of STHXs increase gradually with the increase of the shell-side volume flow, but h/ΔP decreases gradually. Compared with h/ΔP of STHXsSB, that of STHXsPB increases by 62.2–65.7%, and that of STHXsFB increases by 73.9–76.1%. The stresses around the holes of the baffles are higher than other parts of the baffles. Besides, the effect of temperature on the baffle stress distribution is much greater than that of pressure. Although the maximum stress of STHXsFB is the highest, it is in the allowable stress range of the material. Hence, STHXsFB is suitable for water chillers due to its excellent comprehensive performance.